KEHIDUPAN JALAN RODA KOTA MANADO - Ginano, Anugerah B. R.; Kusen, Albert W. S.; Mawara, Jetty E. T. (Universitas Sam Ratulangi, 2018)
Waroeng coffee is places that are specially serving coffee as a main, and offers of another menu. In Manado City there are various locations that serve as a place of drinking coffee, either served up with modern ways as in mall that many of the right now, as starbucks, coffee bean & tea leaf, and excelso, the majority of urban visitor are people that has established the condition of the economy. In addition in places is simple, like in Kecamatan Sario, Sam Ratulangi Street, including also in the area of the Jalan Roda.Jalan Roda not only has become a location for of drinking coffee, their actions but also the location of hang-out. They come not only ways to provide stroking each other, look arround, meet old the friend, but some of them to the discussion, to set up in business, from playing the chess and enjoying delights as special meal of Manado.Activities occurring in Jalan Roda that at this point has been a center for meeting by a government official, entrepreneurs, activists, students, and artist which the in it increase regional income in the field of economy so the Jalan Roda by a government Manado City, used as a culinary tourist destination able to provide employment opportunities.Â Keywords: coffee, drinking, culinaryÂ